2021
DOI: 10.3389/fnagi.2021.697621
|View full text |Cite
|
Sign up to set email alerts
|

Functional Aging in Male C57BL/6J Mice Across the Life-Span: A Systematic Behavioral Analysis of Motor, Emotional, and Memory Function to Define an Aging Phenotype

Abstract: Aging is characterized generally by progressive and overall physiological decline of functions and is observed in all animals. A long line of evidence has established the laboratory mouse as the prime model of human aging. However, relatively little is known about the detailed behavioral and functional changes that occur across their lifespan, and how this maps onto the phenotype of human aging. To better understand age-related changes across the life-span, we characterized functional aging in male C57BL/6J mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
112
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 123 publications
(184 reference statements)
15
112
2
2
Order By: Relevance
“…To determine whether prolonged olfactory bulb inflammation was correlated with altered metrics on assays that assess affective behaviors, mock-, IAV-, and SARS-CoV-2-treated hamsters were subjected to a marble burying assay (Figure 6G-I). When hamsters were subjected to the this assay, an established metric for assessing rodent repetitive and anxiety-like behaviors (Yanai and Endo, 2021), SARS-CoV-2-infected animals demonstrated a significant reduction in burying activity compared to both mock and IAV groups, which performed comparably and were thus grouped together (Figure 6G). While several studies consider increased burying as a sign of elevated compulsiveness or anxiety-like behaviors, other studies have found that anxiogenic or compulsive behavior-inducing pharmacological substances can actually cause decreases in marble burying behavior that are well-below baseline (Jimenez-Gomez et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether prolonged olfactory bulb inflammation was correlated with altered metrics on assays that assess affective behaviors, mock-, IAV-, and SARS-CoV-2-treated hamsters were subjected to a marble burying assay (Figure 6G-I). When hamsters were subjected to the this assay, an established metric for assessing rodent repetitive and anxiety-like behaviors (Yanai and Endo, 2021), SARS-CoV-2-infected animals demonstrated a significant reduction in burying activity compared to both mock and IAV groups, which performed comparably and were thus grouped together (Figure 6G). While several studies consider increased burying as a sign of elevated compulsiveness or anxiety-like behaviors, other studies have found that anxiogenic or compulsive behavior-inducing pharmacological substances can actually cause decreases in marble burying behavior that are well-below baseline (Jimenez-Gomez et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The marble burying assay was adapted from previously described protocols (Yanai and Endo, 2021). Hamsters were placed into a corner of a cage with clean bedding that had 20 equally-spaced glass marbles placed inside of it.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, cognitive decline is common between mice and humans [65], including reduction in spatial navigation performance (such as the Morris water maze in mice, or the equivalent in humans) [66]. Despite this, mouse cognitive decline seems to appear relatively sooner and faster than for humans [67], and decline in elaborate cognitive abilities specific to human, such as language, cannot be tested in animal models. Further, the neurogenic niche inhibited by T cells in aged mice [26] may not exist in humans [68].…”
Section: Discussionmentioning
confidence: 99%
“…The results of escape latency in the MWM test were examined through three-way mixed ANOVA (Champagne et al 2002 ). For the total traveling distance, platform crossing counts, the duration and distance in the target zone and the fear conditioning tests were assessed with two-way ANOVA (Yanai and Endo 2021 ). Other data were assessed with two-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%